Alpine Waters - Bundi, Ulrich; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
Most of the world$1 (Bs mountains are rich in water and, as such, play a pivotal role in the global water cycle. They provide water for diverse human uses and ecosystems. Growing water demands as well as climate change will lead to ever-increasing pressure on mountain waters. Overcoming water-use conflicts and maintaining the ecological functioning of mountain waters presents a highly challenging task and is indispensable for sustainable development. This book extensively portrays the highly diverse attributes of mountain waters and demonstrates their paramount importance for ecological and societal development. The extensive summaries on the scientific basics of mountain waters are supplemented with considerations on the diverse water uses, needs for management actions, and challenges regarding sustainable water management. This overview concerns not only the mountain areas themselves but also downriver reaches and their surrounding lowlands, and, therefore, the relationship between mountain and lowland water issues.s
Synthesis: Features of Alpine Waters and Management Concerns -- Alpine Water Resources -- General Characteristics of Alpine Waters -- Impact of Climate Change on Water Resources in the Alpine Regions of Switzerland -- Human Interventions -- Biogeochemistry and Pollution of Alpine Waters -- Water Chemistry of Swiss Alpine Rivers -- Effect of Acid Deposition on Chemistry and Biology of High-Altitude Alpine Lakes -- Alpine Glaciers as Archives of Atmospheric Deposition -- Persistent Organic Contaminants in Alpine Waters -- Ecology of Alpine Waters -- Water Sources and Habitat of Alpine Streams -- Biodiversity of Flora and Fauna in Alpine Waters -- Case Studies -- Integrated Environmental Management of Hydropower Operation Under Conditions of Market Liberalization -- Downstream Relevance of Reservoir Management -- A Plea for the Restoration of Alpine Rivers: Basic Principles Derived from the (3z(BRhone-Thur(3y (BCase Study -- Water Management Challenges in Himalayan Watersheds.s
Keywords: Environmental sciences; Analytical biochemistry; Geochemistry; Hydraulic engineering; Aquatic biology; Environmental chemistry; Environmental pollution; Environment; Environmental Chemistry; Hydrogeology; Freshwater & Marine Ecology; Geochemistry; Waste Water Technology / Water Pollution Control / Water Management / Aquatic Pollution; Analytical Chemistry